IMPLEMENTASI KEBIJAKAN RETRIBUSI JASA USAHA PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH (KASUS RETRIBUSI RUMAH DINAS) - Mateka, Sintiadewi (Katalogis, 2015)
This study aims at determining the implementation of service business retribution policy of local government, Central Sulawesi (retribution case of official residence) conducted by the Department of Revenue, Central Sulawesi. This is a qualitative research in term of descriptive method. The informants of this research were 6 people consisting of 4 employees of the Regional Revenue Office of Central Sulawesi, one Revenue Treasurer of Department of Water Resources and one informant of compulsory levy. The informants were chosen by using purposive sampling technique. This research uses primary data and secondary data. Techniques of the data collection are observations, interviews, documentations, and triangulation. The data were analyzed by using Miles and Huberman, data reduction, data presentation and concluding. The theory used was Edward III theory consisting of four aspects namely Communication, Resource, Disposition, Bureaucracy Structure. The result of the research shows that the implementation of official residence retribution which covering Communication, Resource, Disposition, Bureaucracy Structure, is not effective yet. First, the communication aspect did not run effectively because socialization about the policy was considerably minimum, the consistency of Local Revenue Department in implementing the policy did not run effectively because some parts of the policy were not implemented well. Second, Resources were inadequate. Personnel resources, equipment resources and the resources of funds caused the policy implementers have not been able to work according to their competence and professionalism. Third, the disposition aspect has not run as expected, lack of awareness of the implementers to remain on the policy objectives. Fourth, the absence of operational standards and procedures (SOP) about the standard retribution of official residence, causing the policy implementers and policy targets (compulsory levy) act without any clear guidelines regarding the official residence retribution. Thus the researcher concludes that the implementation of the charges for services policy of Central Sulawesi (retribution case of official residence) has not run as expected.